Spinal fusion surgery blood loss: a narrative review abstract (Research, Society and Development, 2022)
Spinal fusion surgeries are commonly associated to great blood losses that, besides being able to directly harm the procedure, can be associated to a higher risk of serious complications due to the blood transfusion needed afterwards. Therefore, the present study aims to review the literature towards blood loss in different techniques of spinal fusion. For this, nine studies were selected, being two of them about cervical spine fusion, two of them about thoracic spine fusion and five of them about lumbar spine fusion, to compare and analyze twelve different techniques. The spinal fusion in thoracic and lumbar interbody arthrodesis were the ones that shown greatest blood loss.